New challenges in the use of nanomedicine in cancer therapy. Issue 1 (1st January 2022) - Rasool, Mahmood; Malik, Arif; Waquar, Sulayman; Arooj, Mahwish; Zahid, Sara; Asif, Muhammad; Shaheen, Sumaira; Hussain, Abrar; Ullah, Hamid; Gan, Siew Hua
ABSTRACT: Nanomedicines are applied as alternative treatments for anticancer agents. For the treatment of cancer, due to the small size in nanometers (nm), specific site targeting can be achieved with the use of nanomedicines, increasing their bioavailability and conferring fewer toxic side effects. Additionally, the use of minute amounts of drugs can lead to cost savings. In addition, nanotechnology is effectively applied in the preparation of such drugs as they are in nm sizes, considered one of the earliest cutoff values for the production of products utilized in nanotechnology. Early concepts described gold nanoshells as one of the successful therapies for cancer and associated diseases where the benefits of nanomedicine include effective active or passive targeting. Common medicines are degraded at a higher rate, whereas the degradation of macromolecules is time-consuming. All of the discussed properties are responsible for executing the physiological behaviors occurring at the following scale, depending on the geometry. Finally, large nanomaterials based on organic, lipid, inorganic, protein, and synthetic polymers have also been utilized to develop novel cancer cures. GRAPHICAL ABSTRACT: uf0001